Developing a Guide Book of Project-Based Learning Utilizing Tiktok Videos for Online English Classes - Dwi Susanto Ali Purwoko; Regina Regina; Iksanudin Iksanudin (Universitas Muhammadiyah Kalimantan Timur, 2023)
The pandemic has migrated learning activities from offline to online as the effort to break the chain of the spread of Covid 19. Capability in utilizing technology in teaching is essential to support teaching English activities. Developing the appropriate learning model and instruction media in current situation is required to create the online teaching learning activities to be more innovative, attractive and effective. Based on the need analysis obtained from the English teachers who joint BIMTEK of TikTok as teaching Media, they have experienced implementing learning model proposed by Kemendikbud (Project-Based), but they have not utilized TikTok as teaching media. Therefore, the purpose of research is to develop a guide book of project-based learning utilizing TikTok videos for online classes. Development research was used in this research based on ADD. The data were collected through questionnaires, field notes, and participants’ reflection and comments. The data indicated that providing the appropriate learning model by utilizing the familiar media among the students in current situation is needed to ensure the English teaching activities are acceptable in giving meaningful experiences for the students who learn from their respective homes. The result of this research is a guide book of TikTok Project Based teaching consisted of learning model implemented (project-based learning), the media utilization (TikTok videos), the sample of project-based TikTok activities, the sample of material designs, and video tutorials.